A proposal for cellularity assessment for EGFR mutational analysis with a correlation with DNA yield and evaluation of the number of sections obtained from cell blocks for immunohistochemistry in non-small cell lung carcinoma. Issue 7 (5th January 2016) - da Cunha Santos, Gilda; Wyeth, Tyler; Reid, Allie; Saieg, Mauro Ajaj; Pitcher, Bethany; Pintilie, Melania; Kamel-Reid, Suzanne; Tsao, Ming Sound
Abstract : Aims: Different approaches have been described for reporting specimen adequacy for epidermal growth factor receptor ( EGFR ) mutation analysis. We aimed: (1) to conduct cellularity assessment and to investigate its association with DNA yield, (2) to compare the H&E slides taken before and after the thick sections (curls) obtained for EGFR testing and (3) to evaluate the number of ancillary studies performed. Methods: Cell block (CB) slides of 110 non-small cell lung carcinoma cases submitted to EGFR analysis from 2010 to 2012 were reviewed for total cellularity (ranges 1–100, 100–250, 250–500, 500–750, 750–1000 and >1000 cells), tumour cellularity (ranges 1–50, 50–100, 100–300 and >300 cells) and the percentage of tumour cells. Precurl and postcurl H&E slides were compared using the three criteria. The number of immunohistochemistry (IHC) markers and special stains and DNA yield were recorded. Results: DNA yield was significantly associated with the total cellularity, number and percentage of tumour cells. For 46 cases with precurl and postcurl slides, only three (6.5%) were classified as being different and in two of them the postcurl slide had greater cellularity than the precurl. IHC was performed in 83 cases, with a minimum of 1 and a maximum of 11 markers (median of 3) per case. Conclusions: An association between the total cellularity and the tumour cellularity with the DNA yield was demonstrated using the ranges described. Evaluation of a postcurl slide is an unnecessary practice. The majority of the CB had sufficient material for ancillary studies (up to 11 markers) and mutation testing.